The Role of Local Governments in the Development of Village-Owned Enterprise in Sambas Regency - Arief Maulana; Reza Pratama Riansyah; Eka Yuliana Rahman (Universitas Medan Area, 2022)
This study aims to analyze and explain the strategy of Sambas Regency to develop Village-Owned Enterprises to improve the community's economy. This study also examines the obstacles/constraints experienced by local governments in developing Village-Owned Enterprises in their regions. The authors used qualitative methods with case study variants and literature studies as data collection techniques. The results of this study indicate that the role of the Sambas Regency Government in fostering Village-Owned Enterprises is felt to be getting better, as indicated by its role through the Agency of Social and Village Community Empowerment Services which always facilitates village government and Village-Owned Enterprises management by providing training, coaching, and supervision. In addition, the management of Village-Owned Enterprises is still quite difficult due to problems such as limited human resources. Until now, there are still many obstacles that must be resolved by the local government or the Village-Owned Enterprises managers themselves.